Lasius flavus - Collingwood, C. A. (Zenodo, 1979)
33. Lasius flavus (Fabricius, 1781) Figs. 124-127. Formica flava Fabricius, 1781:491. Worker. Clear yellow to brownish yellow. Body hairs on dorsum of gaster and alitrunk long; appendages and body covered with more or less thick adpressed pubescence, more dilute on head. No erect hairs on tibiae, scapes or genae. Scale thin in side view, low and broad in front view with dorsal margin mildly convex straight or in larger specimens occasionally emarginate. Size very variable in North European populations. Length: 2.2-4.8 mm. Queen. Light to dark brown with underside paler. Pubescence and pilosity as in worker. Head distinctly narrower than alitrunk. Eyes with numerous short hairs. Wings partly infuscate. Length: 7.2-9.5 mm. Male: Dark brown to brownish black. Scape and tibial hairs entirely lacking; head narrower than alitrunk; mandibles with one apical and pre-apical tooth. Vein m-cu often missing on fore-wing but usually present in extreme northern populations. Wings faintly tinted but not infuscate. Length: 3.5-5.0 mm. Distribution. Throughout Denmark and Southern Fennoscandia up to latitude 67°; one record for Polmark in the Norwegian Finnmark. - Throughout British Isles excluding Northern Islands. - Range: North America to Japan; North Africa to Arctic. Biology. This species is very widely distributed and one of the most abundant in North Europe where it is a characteristic earth mound builder in pastures and along the periphery of woodlands but also nesting under stones in rocky areas. Colonies are started by one or more queens with primary pleometrose quite frequent. In North Europe nests in exposed places and in northern extremity of its distribution, L. flavus exhibits a wide range of worker size. On warm sites in southern areas usually in sandy lowland heath, worker size is small and much less variable. Eye ommatidium number is correlated with size and series of small workers with eyes with low ommatidium number are sometimes referred to Lasius myops Forel. However, queen size is constant regardless of worker size. L. myops is therefore regarded as a synonym of L. flavus. Individual nests may contain several thousand individuals and favourable nest sites, e. g. pasture sloping with a southern aspect, may be crowded with mound nests. This species, as with L. niger, tends to swarm on the same day in any one area and in years of abundant production of sexuals huge mating may occur during late July or August. This species is hypogoeic, seldom occurring above ground, feeding on small insects and the exudate of subterranean root feeding aphids. : Published as part of Collingwood, C. A., 1979, The Formicidae (Hymenoptera) of Fennoscandia and Denmark., pp. 1-174 in Fauna Entomologica Scandinavica 8 on page 96